Function-structure approach reveals novel insights on the interplay of Immunoglobulin G 1 proteoforms and Fc gamma receptor IIa allotypes - Lippold, Steffen; Mistry, Karishma; Lenka, Sunidhi; Whang, Kevin; Liu, Peilu; Pitschi, Sebastian; Kuhne, Felix; Reusch, Dietmar; Cadang, Lance; Knaupp, Alexander; Izadi, Saeed; Dunkle, Alexis; et al. (Frontiers in Immunology, 2023)
Human Fc gamma receptor IIa (FcγRIIa) or CD32a has two major allotypes with a single amino acid difference at position 131 (histidine or arginine). Differences in FcγRIIa allotypes are known to impact immunological responses such as the clinical outcome of therapeutic monoclonal antibodies (mAbs). FcγRIIa is involved in antibody-dependent cellular phagocytosis (ADCP), which is an important contributor to the mechanism-of-action of mAbs by driving phagocytic clearance of cancer cells. Hence, understanding the impact of individual mAb proteoforms on the binding to FcγRIIa, and its different allotypes, is crucial for defining meaningful critical quality attributes (CQAs). Here, we report a function-structure based approach guided by novel FcγRIIa affinity chromatography-mass spectrometry (AC-MS) assays to assess individual IgG1 proteoforms. This allowed to unravel allotype-specific differences of IgG1 proteoforms on FcγRIIa binding. FcγRIIa AC-MS confirmed and refined structure-function relationships of IgG1 glycoform interactions. For example, the positive impact of afucosylation was higher than galactosylation for FcγRIIa Arg compared to FcγRIIa His. Moreover, we observed FcγRIIa allotype-opposing and IgG1 proteoform integrity-dependent differences in the binding response of stress-induced IgG1 proteoforms comprising asparagine 325 deamidation. The FcγRIIa-allotype dependent binding differences resolved by AC-MS were in line with functional ADCP-surrogate bioassay models. The molecular basis of the observed allotype specificity and proteoform selectivity upon asparagine 325 deamidation was elucidated using molecular dynamics. The observed differences were attributed to the contributions of an inter-molecular salt bridge between IgG1 and FcγRIIa Arg and the contribution of an intra-molecular hydrophobic pocket in IgG1. Our work highlights the unprecedented structural and functional resolution of AC-MS approaches along with predictive biological significance of observed affinity differences within relevant cell-based methods. This makes FcγRIIa AC-MS an invaluable tool to streamline the CQA assessment of therapeutic mAbs.